2012
DOI: 10.1080/00140139.2012.692819
|View full text |Cite
|
Sign up to set email alerts
|

Association between spinal loads and the psychophysical determination of maximum acceptable force during pushing tasks

Abstract: The objective of this study was to investigate potential associations between an individual's psychophysical maximum acceptable force (MAF) during pushing tasks and biomechanical tissue loads within the lumbar spine. Ten subjects (eight males, two females) pushed a cart with an unknown weight at one push every two minute for a distance of 3.9 m. Two independent variables were investigated, cart control and handle orientation while evaluating their association with the MAF. Dependent variables of hand force and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Therefore, before weighting factors for an alternative calculation method can be determined empirically, further research is needed on the question of which indicator represents the bottleneck for specific types of physical work activities, and should be used to calculate cumulative loading. Spearman's correlation coefficients show the greatest correlation between load intensity and both rate of HR change (.386) and RPE (.460), although the RPE may to some extent be influenced by the use of handheld weights, since Le et al (2012) have shown that psychophysical parameters when handling loads depend on tactile sensations of the hands. Due to the periodic nature of the loading conditions shown in Figure 4, a doubling of the area under the loading curve leads to a doubling of the duration of the lifting/lowering task.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, before weighting factors for an alternative calculation method can be determined empirically, further research is needed on the question of which indicator represents the bottleneck for specific types of physical work activities, and should be used to calculate cumulative loading. Spearman's correlation coefficients show the greatest correlation between load intensity and both rate of HR change (.386) and RPE (.460), although the RPE may to some extent be influenced by the use of handheld weights, since Le et al (2012) have shown that psychophysical parameters when handling loads depend on tactile sensations of the hands. Due to the periodic nature of the loading conditions shown in Figure 4, a doubling of the area under the loading curve leads to a doubling of the duration of the lifting/lowering task.…”
Section: Discussionmentioning
confidence: 99%